Age-related differences in the relationship between confidence and false memory in a mnemonic discrimination task - Ágnes Szőllősi; Dorottya Bencze; Soma Zsebi; Eszter Juhász; Mihály Racsmány (Scientific Reports)
Abstract In addition to episodic memory loss there is an increase in false remembering in ageing especially when the discrimination between studied and new items is difficult in a recognition memory task. The aim of this study was to identify the underlying psychological mechanisms of this behavior, specifically, the possible role of false recollection. We used the Mnemonic Similarity Task, a widely used task in neuroscience research developed to assess the behavioral manifestation of hippocampal computations, pattern separation and pattern completion. First, older and young adults (n = 39 and 44, respectively) were presented with images of everyday objects. Then, on a surprise recognition test, they saw old (studied) and new (non-studied) items as well as visually similar lures of the images seen in the study phase. Instead of using the original Old/New test format, we asked participants to make confidence judgments. Our response frequency and ROC (receiver operating characteristics) analyses revealed overconfidence in false memories for the lures in the group of older adults suggesting false recollection. Such overconfidence was not observed for the completely new stimuli. Our results imply that older adults tend not to acknowledge some memory problems as a consequence of very high confidence in false memories.